2018
DOI: 10.1186/s12970-018-0248-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of professional Australian football athletes surrounding body composition assessment

Abstract: BackgroundSports Dietitians aim to assist in improving performance by developing nutrition knowledge (NK), enhancing dietary intake and optimising body composition of athletes. In a high-pressure environment, it is important to identify factors that may compromise an athlete’s nutrition status. Body composition assessments are regularly undertaken in sport to provide feedback on training adaptions; however, no research has explored the impact of these assessments on the dietary intake of professional athletes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
3
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 37 publications
9
100
3
10
Order By: Relevance
“…Potential food shortages in this area may generate decreased exercise capacity owing to the special role of carbohydrates in the energy of physical exercise, of calcium in regulating skeletal muscle contractions, and of antioxidant vitamins in eliminating the effects of oxidative stress developing under the conditions of intense physical exercise [1][2][3][4][5]. the observed nutritional anomalies corresponded with tendencies described by other authors in various groups of athletes performing team and individual disciplines, including Polish team sports players [9,13,14], professional English footballers [15], professional british rugby players [16], Australian football players [17], Lithuanian sportsmen of endurance disciplines [18], women training medium-and long-distance running [19], racecar drivers [20], and Portuguese athletes [21]. the following were found in the case of the Lithuanian endurance disciplines: carbohydrate deficiencies (80.8%) and excess fats, saturated fatty acids and cholesterol (> 70%) [18].…”
Section: Discussionsupporting
confidence: 63%
“…Potential food shortages in this area may generate decreased exercise capacity owing to the special role of carbohydrates in the energy of physical exercise, of calcium in regulating skeletal muscle contractions, and of antioxidant vitamins in eliminating the effects of oxidative stress developing under the conditions of intense physical exercise [1][2][3][4][5]. the observed nutritional anomalies corresponded with tendencies described by other authors in various groups of athletes performing team and individual disciplines, including Polish team sports players [9,13,14], professional English footballers [15], professional british rugby players [16], Australian football players [17], Lithuanian sportsmen of endurance disciplines [18], women training medium-and long-distance running [19], racecar drivers [20], and Portuguese athletes [21]. the following were found in the case of the Lithuanian endurance disciplines: carbohydrate deficiencies (80.8%) and excess fats, saturated fatty acids and cholesterol (> 70%) [18].…”
Section: Discussionsupporting
confidence: 63%
“…Mistakes and qualitative nutritional errors found in the examined group of athletes, generally corresponded to the trends described in other studies conducted at both Polish and foreign centres, among competitive athletes of various disciplines. In these studies, the inadequate consumption of some groups of foods with high nutritional density was confirmed, including vegetables and fruits, wholegrains, dairy products and fish, considering Polish athletes participating in team [13] and individual disciplines [18], as well as Spanish [44], Iranian [27] and Portuguese athletes [34], as well as English and Australian footballers [26,35], Irish and British rugby players [1,45], Lithuanian athletes of endurance disciplines [3], women training mediumand long-distance running [22] and rally drivers [2].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that Australian athletes have low NK scores and fail to comply with best‐practice sports nutrition guidelines . As NK is one factor that can influence nutrition behaviour, it is pertinent to explore the preferred information sources that athletes use, and how preferences influence NK.…”
Section: Discussionmentioning
confidence: 99%
“…Data for previous sources of advice, preferred sources of nutrition information and preferred types of nutritioneducation support were assessed for the whole cohort and stratified based on age (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), ≥36 years), gender (male, female), level of education (high school, diploma and university), and level of sport played (elite, non-elite). Differences in these responses based on participant characteristics were assessed using χ 2 analysis.…”
Section: Methodsmentioning
confidence: 99%